Perioperative considerations and complications in pediatric parathyroidectomy. (December 2016) - Hanba, Curtis; Bobian, Michael; Svider, Peter F.; Sheyn, Anthony; Siegel, Bianca; Lin, Ho-Sheng; Raza, S. Naweed
Abstract: Objectives/Hypothesis: To evaluate perioperative considerations and post-operative complications associated with parathyroidectomy in the pediatric population. Methods: The Kids' Inpatient Database 21 (KID) was searched for patients who underwent parathyroidectomy in 2009 and 2012. Patient demographics, hospital stay, associated charges, and post-operative adverse sequelae were evaluated in all patients and included patient comorbidity and additional procedure requirement analysis. Results: There were 182 patients extrapolating to 262 parathyroidectomies over the two years analyzed. Although a minority of patients were male (45.4%), these patients had greater rates of complications, length of stay, and hospital charges. Importantly, minorities and younger patients (≤15y) also had more complicated post-operative courses. The lengths of stay for patients experiencing post-operative altered mental status (18.7d), post-operative infection (15.5d), respiratory complications (19d), and cardiac complications (13d) were significantly increased compared to individuals without major complications (3.4d) (p < 0.001). Patients with pre-existing chronic kidney disease, dialysis-dependence, and bone sequelae (most commonly from hungry bone syndrome) also had significantly lengthier stays and greater associated costs. Conclusion: Findings from this analysis can be included in a comprehensive pre-operative informed consent process between physicians and patients discussing perioperative considerations and potential complications of parathyroidectomy. Males, younger children, and patients with preexisting renal conditions experienced lengthier and more complicated hospital stays, suggesting the need for closer monitoring of these cohorts.